PEMANFAATAN Caulerpa spp. SEBAGAI BAHAN MINUMAN DIVERSIFIKASI BOBA DI GAMPONG COT KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Hayatun Nufus; M. Ali Sarong; Alaudin Alaudin; Sri Wahyuni; Eka Lisdayanti; Asri Mursawal; M. Agam Thahir; Zulfadhli Zulfadhli (Universitas Teuku Umar, 2022)
This socialization to the community will be carried out in September 2022 in Gampong Cot, Samatiga District, West Aceh Regency. Boba making practice aims to train people in making boba drinks using Caulerpa spp. efforts to improve the regional economy. Implementation of socialization using theory and training with the lecture method. The results of the service can be practiced well, smoothly, structured and successfully involve the Gampong Cot community, the implementation process consists of 4 stages. At the stage of training and mentoring in making ice boba Caulerpa spp. consists of two sessions, namely a theory session and a training session. The theory session contains the presentation of Caulerpa spp. in general and its contents, while the training session contained 1) selection of mature Caulerpa spp to be harvested or collected from the site, 2) milling of Caulerpa spp. become smooth using a blender, 3) mixing Caulerpa spp. with other ingredients, 4) print boba using a printing machine, 5) boil boba, and 6) make boba ice as desired.